Physico-chemical parameters and primary productivity of a fish pond of Madhumara, Biratnagar - Chhetri, Purna Bahadur; Chhetry, Damodar Thapa (Nepalese Journal of Biosciences, 2013)
The physico-chemical parameters and primary productivity of a fish pond of Madhumara, Biratnagar was studied from October 2007 to September 2008. The maximum air and water temperature and water transparency were recorded in rainy season, whereas maximum pH, dissolved oxygen and chloride were recorded in winter season. Free carbon dioxide and total hardness were maximum in summer season. The gross primary productivity, net primary productivity and community respiration were found maximum in winter season.